Preparation method of fireproof soundproof insulation board
Patent Information
- Application Number
- CN202611226496.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明提供一种防火隔音保温板的制备方法,解决相关技术中保温板防火性能、隔音性能与保温性能难以协同提升,且材料疏水耐久性不足的技术问题
本发明通过对二氧化硅气凝胶微球进行甲基三甲氧基硅烷疏水改性,在纳米孔道内壁形成共价键合的疏水单分子层,阻止碱性溶液经毛细作用渗入纳米孔道,从而避免碱侵蚀引起的骨架溶解和孔结构坍塌,使疏水改性二氧化硅气凝胶微球在板材服役过程中保持超低导热特性;采用钾基碱激发剂替代传统钠基碱激发剂,利用钾离子离子半径较大、易被铝硅酸盐四面体网络骨架结构空腔捕获固定的特点,降低游离碱金属离子含量,从源头减少泛碱驱动力;引入活性氧化铝微粉提供额外铝源,促进高交联度网络骨架形成,增强对碱金属离子的束缚能力;引入纳米氧化锌在碱性环境中原位生成层状锌酸盐,填充孔壁微缺陷并阻断离子迁移通道。
Smart Images

Figure CN123003199A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical synthesis technology, and more specifically, to a method for preparing a fireproof, soundproof, and heat-insulating board. Background Technology
[0002] Fire-resistant, sound-insulating, and heat-insulating boards for buildings play a vital role in building energy conservation and safety. In existing technologies, most fire-resistant, sound-insulating, and heat-insulating boards use geopolymers as the inorganic cementitious matrix, incorporating ultra-low thermal conductivity components such as silica aerogel microspheres to reduce the board's thermal conductivity, and utilizing the inorganic properties of the geopolymer matrix to achieve fire resistance.
[0003] Existing technologies typically employ sodium-based activators to activate aluminosilicate precursors such as metakaolin to prepare geopolymer matrices, and then directly disperse unmodified silica aerogel microspheres in an alkaline slurry.
[0004] The aforementioned existing technology suffers from two coupled degradation problems. First, the nanoporous framework of silica aerogel microspheres is eroded by alkaline slurry in the high ionic strength environment, leading to pore structure collapse and loss of ultra-low thermal conductivity. Second, in the sodium-based polymer system, free sodium ions migrate to the surface of the board with moisture under humid and hot conditions and precipitate carbonate crystals. The crystallization pressure generated by crystal growth damages the pore wall structure of the matrix, while the alkaline precipitates continuously erode the surface of the silica aerogel microspheres. These two failures promote each other, resulting in a continuous deterioration of the thermal insulation and sound insulation performance of the board during service. Summary of the Invention
[0005] This invention provides a method for preparing a fireproof, soundproof, and heat-insulating board, which solves the technical problems in related technologies where it is difficult to synergistically improve the fireproof performance, sound insulation performance, and heat insulation performance of the insulation board, and where the material has insufficient hydrophobic durability.
[0006] This invention discloses a method for preparing a fireproof, soundproof, and heat-insulating board, comprising the following steps: Silica aerogel microspheres were prepared by sol-gel method and supercritical carbon dioxide drying, and hydrophobically modified with methyltrimethoxysilane; geopolymer precursor powder was obtained by dry mixing metakaolin, slag powder, activated alumina powder and silica fume. Potassium hydroxide and potassium silicate are used to prepare a potassium-based base activator solution; the geopolymer precursor powder is mixed with the potassium-based base activator solution to obtain a potassium-based polymer slurry; After adding nano zinc oxide suspension to the potassium-based polymer slurry and mixing, hydrophobically modified silica aerogel microspheres, aluminum silicate short fibers, hydrogen peroxide aqueous solution and sodium dodecyl sulfate are added in sequence and stirred to obtain foamed composite slurry; The foamed composite slurry is poured and foamed into shape, and after curing and drying, the surface is coated with an organosilicon acrylic copolymer emulsion to form a hydrophobic sealing layer, thus obtaining a fireproof, soundproof and heat-insulating board.
[0007] Furthermore, the silica aerogel microspheres have a porosity of 90% to 95% and a specific surface area of 600 to 900 m². 2 / g, with an average pore size of 8 to 20 nm; the conditions for drying the supercritical carbon dioxide are a temperature of 40 to 50 °C, a pressure of 10 to 14 MPa, and a drying time of 4 to 8 h.
[0008] Furthermore, the hydrophobic modification uses a hexane solution of methyltrimethoxysilane as the modifying liquid, the mass fraction of methyltrimethoxysilane is 3% to 8%, the modification reaction temperature is 25 to 35°C, and the reaction time is 2 to 4 hours; after modification, the water contact angle of the hydrophobic modified silica aerogel microspheres is 140° to 155°.
[0009] Further, the geopolymer precursor powder comprises 50 to 70 parts by weight of metakaolin, 15 to 25 parts by weight of slag powder, 5 to 12 parts by weight of activated alumina powder, and 8 to 15 parts by weight of silica fume; the activated alumina powder is γ-phase alumina with a specific surface area of 150 to 280 m². 2 / g.
[0010] Furthermore, the potassium-based activator solution is prepared by dissolving 4 to 8 parts by weight of potassium hydroxide in 18 to 28 parts by weight of deionized water, cooling to room temperature, and then adding 15 to 25 parts by weight of potassium silicate with a modulus of 1.4 to 2.0; the solid content of the potassium silicate is 30% to 45%.
[0011] Furthermore, the primary particle size of the nano-zinc oxide is 20 to 50 nm, and the specific surface area is 30 to 60 m². 2 / g; The nano zinc oxide suspension is prepared by dispersing 1 to 3 parts by weight of nano zinc oxide in 4 to 12 parts by weight of deionized water and then ultrasonically dispersing for 10 to 20 minutes.
[0012] Furthermore, in the foamed composite slurry, the amount of hydrophobically modified silica aerogel microspheres is 15 to 25 parts by weight, the amount of aluminum silicate short fibers is 3 to 6 parts by weight, the amount of 30% hydrogen peroxide aqueous solution is 0.3 to 1.0 parts by weight, and the amount of sodium dodecyl sulfate is 0.2 to 0.6 parts by weight; the mass ratio of the geopolymer precursor powder to the potassium-based activator solution is 1.5:1 to 2.5:1.
[0013] Furthermore, in the casting and foaming molding step, an alkali-resistant glass fiber mesh is pre-laid at the bottom of the mold, with a mesh size of 4mm×4mm to 6mm×6mm; the foaming temperature is 45 to 60℃, and the static foaming and initial setting time is 3 to 5 hours; the curing and drying includes curing at a temperature of 70 to 85℃ and a relative humidity of 70% to 90% for 48 to 96 hours, and after demolding, drying at 105 to 120℃ until the moisture content is less than 3%.
[0014] Furthermore, the solid content of the organosilicon acrylic copolymer emulsion is 40% to 55%, the coating amount is 8 to 15 parts by weight, and the dry film thickness is 80 to 150 μm; before coating, the surface of the plate is polished to an arithmetic mean roughness of 5 to 15 μm.
[0015] This invention discloses a fireproof, soundproof, and heat-insulating board, which is prepared by the above-described method.
[0016] The beneficial effects of this invention are as follows: This invention modifies silica aerogel microspheres with methyltrimethoxysilane to form a covalently bonded hydrophobic monolayer on the inner wall of the nanopores. This prevents alkaline solutions from penetrating into the nanopores via capillary action, thus avoiding skeletal dissolution and pore structure collapse caused by alkali corrosion. This allows the hydrophobically modified silica aerogel microspheres to maintain ultra-low thermal conductivity during the service life of the substrate. A potassium-based alkali activator is used instead of a traditional sodium-based alkali activator. The large ionic radius of potassium ions and their ease of capture and fixation by the aluminosilicate tetrahedral network cavities reduce the content of free alkali metal ions, thereby reducing the driving force for alkali blooming at its source. Activated alumina micropowder is introduced to provide an additional aluminum source, promoting the formation of a highly cross-linked network framework and enhancing the binding capacity for alkali metal ions. Nano-zinc oxide is introduced to generate layered zincates in situ in an alkaline environment, filling micro-defects in the pore walls and blocking ion migration channels.
[0017] This invention solves the technical problem of continuous decline in the thermal insulation and sound insulation performance of silica aerogel microspheres due to alkali erosion and efflorescence coupling degradation, and achieves the technical effect of maintaining the stability of fireproof, sound insulation and thermal insulation functions of the board in humid and hot service environments. Attached Figure Description
[0018] Figure 1 This is a process flow diagram of the preparation process of the fireproof, soundproof and heat-insulating board provided in the embodiments of the present invention; Figure 2 This is a schematic diagram comparing the thermal conductivity of the embodiments and comparative examples before and after damp heat aging provided in this invention. Figure 3 This is a schematic diagram showing the rate of change of thermal conductivity and the retention rate of specific surface area of aerogel microspheres after wet heat aging of various samples provided in the embodiments of the present invention. Figure 4This is a schematic diagram comparing the sound insulation and compressive strength of the embodiments and comparative examples provided in this invention before and after damp heat aging; Figure 5 This is a schematic diagram of the SEM morphology of the hydrophobically modified silica aerogel microspheres provided in the embodiments of the present invention; Figure 6 This is a schematic diagram of the SEM comparison of the sample cross-section after damp heat aging provided in the embodiments of the present invention (Example 2 vs Comparative Example 1); Figure 7 This is a schematic diagram of the FTIR spectrum of the hydrophobically modified silica aerogel microspheres provided in the embodiments of the present invention; Figure 8 This is a schematic diagram of the TGA thermogravimetric analysis curve of the geopolymer aerogel composite plate provided in an embodiment of the present invention. Detailed Implementation
[0019] The subject matter described herein will now be discussed with reference to exemplary embodiments. It should be understood that these embodiments are discussed only to enable those skilled in the art to better understand and implement the subject matter described herein, and changes may be made to the function and arrangement of the elements discussed without departing from the scope of this specification. Various processes or components may be omitted, substituted, or added as needed in the examples. Furthermore, some features described in the examples may be combined in other examples.
[0020] At least one embodiment of the present invention discloses a method for preparing a fireproof, soundproof, and heat-insulating board, see below. Figure 1 ,include: Step 1: Prepare silica aerogel microspheres.
[0021] 15 to 25 parts by weight of tetraethyl orthosilicate were dissolved in 40 to 60 parts by weight of anhydrous ethanol, and 0.1 to 0.3 parts by weight of oxalic acid and 8 to 12 parts by weight of deionized water were added. The mixture was stirred at 40 to 50 °C for 4 to 8 hours to form a silica sol. The silica sol was transferred to a continuous mineral oil phase and emulsified by stirring at 800 to 1500 rpm to form spherical gel droplets with a particle size of 100 to 300 μm. After aging and gelation, the solution was successively replaced with ethanol and n-hexane, and dried under supercritical carbon dioxide conditions at 40 to 50 °C and 10 to 14 MPa for 4 to 8 hours to obtain silica aerogel microspheres.
[0022] The aforementioned tetraethyl orthosilicate is of analytical grade, with a purity of not less than 98%. During the hydrolysis and polycondensation process, the molar ratio of tetraethyl orthosilicate to deionized water is 1:3 to 1:5, preferably 1:4. The amount of oxalic acid added is adjusted to control the pH of the silica sol within the range of 2.0 to 3.5. This acidic condition is conducive to the formation of a linearly polymerized silica-oxygen framework structure, providing a precursor basis for the subsequent formation of a high-porosity aerogel. The viscosity of the mineral oil continuous phase is 5 to 15 mPa·s (25°C), and the preferred stirring and emulsification speed is 1000 to 1200 rpm. Under these conditions, spherical gel droplets with a particle size of 150 to 250 μm can be stably obtained.
[0023] Furthermore, in the above-mentioned supercritical drying process, the carbon dioxide flow rate is 50 to 120 L / h, and the drying time is preferably 5 to 6 h. Supercritical drying eliminates the damage to the nanoporous framework caused by capillary forces during solvent evaporation, ensuring that the resulting silica aerogel microspheres maintain a porosity of 90% to 95% and a specific surface area of 600 to 900 m². 2 / g, nanoporous structures with average pore sizes of 8 to 20 nm, corresponding to intrinsic thermal conductivity of 0.012 to 0.018 W / (m·K). The porosity was determined by nitrogen adsorption method (BET method), the specific surface area was calculated by BET multi-point method, the average pore size was calculated by nitrogen desorption curve by BJH method, and the thermal conductivity was determined by hot wire method (ASTM C1113).
[0024] Furthermore, after the silica sol is emulsified in the continuous phase of mineral oil, the aging and gelation step is completed by standing at 25 to 35°C for 12 to 24 hours to ensure that the spherical gel droplets are fully cross-linked and cured; in the solvent replacement step, ethanol replacement is repeated 2 to 3 times, with each replacement time being 4 to 8 hours, and n-hexane replacement is repeated 2 to 3 times, with each replacement time being 4 to 8 hours, and the replacement temperature is 25 to 35°C.
[0025] Furthermore, the emulsification step is carried out under a nitrogen protective atmosphere, with a nitrogen introduction rate of 0.1 to 0.3 L / min, to prevent the continuous mineral oil phase from absorbing moisture from the air during stirring and affecting the uniformity of the gel droplets; in the supercritical drying step, the carbon dioxide purity is not less than 99.9% (volume fraction), the pressure increase rate is controlled at 0.2 to 0.5 MPa / min, and the pressure release rate is controlled at 0.1 to 0.3 MPa / min, to avoid the collapse of the nanoporous framework caused by sudden pressure changes.
[0026] Furthermore, after the solvent replacement step is completed, the hexane replacement solution must be recovered by vacuum distillation at a temperature of 60 to 70°C and a pressure of 0.03 to 0.05 MPa. The continuous mineral oil phase can be recycled after being filtered to separate the gel balls. Before recycling, the water content of the mineral oil must be tested. If the water content exceeds 0.1% (mass fraction), it must be dried with anhydrous sodium sulfate before it can be reused.
[0027] Furthermore, the anhydrous ethanol and n-hexane involved in step 1 above are both flammable organic solvents. The operation must be carried out in a fume hood, away from open flames and heat sources. The ethanol vapor generated by the hydrolysis of tetraethyl orthosilicate must be discharged through the ventilation system. The hexane-containing waste liquid and ethanol-containing waste liquid generated by solvent replacement must be collected separately and handed over to a professional waste liquid treatment agency for treatment. They must not be directly discharged into the sewer pipe.
[0028] Step 2: Hydrophobically modified silica aerogel microspheres.
[0029] A modification solution was prepared by dissolving 3 to 8 parts by weight of methyltrimethoxysilane in 92 to 97 parts by weight of n-hexane. The silica aerogel microspheres obtained in step 1 were immersed in the modification solution and reacted at 25 to 35°C for 2 to 4 hours to perform hydrophobic modification. After the reaction, the mixture was filtered and separated. The filter cake was washed 2 to 3 times with n-hexane, each time using 3 to 5 times the mass of the silica aerogel microspheres. The cake was then dried in an oven at 60 to 80°C for 1 to 2 hours to obtain hydrophobically modified silica aerogel microspheres.
[0030] The purity of the aforementioned methyltrimethoxysilane is not less than 97%. The mass fraction of methyltrimethoxysilane in the modification solution is 3% to 8%, preferably 4% to 6%; the mass ratio of methyltrimethoxysilane to n-hexane is 3:97 to 8:92, preferably 5:95. The reaction temperature is preferably 28 to 32°C, and the reaction time is preferably 3 hours. The methyl group in the methyltrimethoxysilane molecule provides a hydrophobic group. After hydrolysis of the three methoxy groups, they undergo a condensation reaction with the silanol groups on the surface of the silica aerogel microspheres, forming a covalently bonded methylsilane monolayer on the inner wall of the nanopores and the outer surface of the microspheres. Under these modification conditions, the water contact angle of the hydrophobically modified silica aerogel microspheres is 140° to 155°, and the hydrophobic layer thickness is at the monolayer level, without clogging the nanopores. The hydrophobically modified silica aerogel microspheres maintain their original ultra-low thermal conductivity. The aforementioned water contact angle is measured using a static drop contact angle meter (GB / T 30693).
[0031] It should be noted that the methylsilane hydrophobic layer reduces the surface free energy of the silica aerogel microspheres. When the hydrophobically modified silica aerogel microspheres are dispersed in an alkaline geopolymer slurry, the high contact angle creates a droplet repulsion effect, preventing the alkaline solution from penetrating into the nanopores via capillary action. This avoids skeletal dissolution and pore structure collapse caused by alkaline erosion, allowing the hydrophobically modified silica aerogel microspheres to maintain an ultra-low thermal conductivity of 0.015 to 0.022 W / (m·K) in the geopolymer matrix. These thermal conductivity values were determined using the hot-wire method (ASTM C1113).
[0032] Furthermore, the above hydrophobic modification step is carried out under a nitrogen protective atmosphere, with a nitrogen introduction rate of 0.05 to 0.15 L / min, to remove moisture and oxygen from the system. Before the modification reaction, the silica aerogel microspheres must be vacuum dried at 60 to 70 °C for 2 to 4 hours (vacuum degree not less than MPa) to remove adsorbed water on the surface of the silica aerogel microspheres, ensuring that the condensation reaction between the methoxy group and the silanol group of methyltrimethoxysilane is fully carried out.
[0033] Furthermore, during the above hydrophobic modification reaction, methyltrimethoxysilane hydrolyzes to produce methanol as a byproduct. Methanol accumulation inhibits the condensation reaction. The filtrate obtained from filtration (containing n-hexane, unreacted methyltrimethoxysilane, and methanol) must be separated by distillation: first, methanol is distilled off at atmospheric pressure and 64 to 66°C; then, n-hexane is recovered at atmospheric pressure and 68 to 70°C. The recovered n-hexane can be recycled for preparing the modified solution. Methanol must be collected separately and treated as hazardous waste; it must not be discharged arbitrarily.
[0034] Furthermore, in step 2 above, n-hexane is a low-boiling-point flammable solvent, and methyltrimethoxysilane is a flammable liquid and irritating. The operation must be carried out in a fume hood, away from open flames and heat sources, and operators must wear protective gloves and goggles. The operation of distilling and recovering n-hexane and methanol must use explosion-proof heating equipment. Methanol is toxic, and inhalation or skin contact can cause harm. When collecting methanol by distillation, the operation must be carried out under ventilation conditions and an organic vapor protective mask must be worn.
[0035] Step 3: Prepare geopolymer precursor powder.
[0036] Mix 50 to 70 parts by weight of metakaolin, 15 to 25 parts by weight of slag powder, 5 to 12 parts by weight of activated alumina powder, and 8 to 15 parts by weight of silica fume in a mixer for 10 to 20 minutes to obtain geopolymer precursor powder.
[0037] The above-mentioned metakaolin was obtained by dehydroxylation activation of calcined kaolin at 700 to 850℃. The content is 40% to 45% (mass fraction). Content is 50% to 55% (mass fraction), and specific surface area is 12 to 20 m². 2 / g, median particle size The range is 3 to 8 μm, of which This represents the particle size corresponding to 50% of the cumulative volumetric particle size distribution. The slag powder is S95 grade granulated blast furnace slag powder with a specific surface area of not less than 400 m². 2 / kg, with an activity index (7d) of not less than 75%. Silica ash Content not less than 92% (mass fraction), specific surface area of 18 to 25 m² 2 / g, median particle size The range is 0.1 to 0.3 μm.
[0038] It should be noted that the activated alumina micro powder is γ-phase alumina with a specific surface area of 150 to 280 m². 2 / g, median particle size The size is 1 to 5 μm. The content is not less than 99% (mass fraction). Activated alumina micropowder provides an additional soluble aluminum source in the alkali-activated system, promoting an increase in the proportion of aluminum-oxygen tetrahedra in the aluminosilicate tetrahedral network, forming a three-dimensional network framework with a higher degree of cross-linking. The high degree of cross-linking enhances the binding ability of alkali metal ions, while simultaneously increasing the density of the matrix structure, improving water resistance and impermeability. The preferred dosage of activated alumina micropowder is 7 to 10 parts by weight.
[0039] Furthermore, the above dry mixing step is carried out at a mixer speed of 100 to 200 rpm to ensure that the components are uniformly dispersed and to avoid local segregation affecting the uniformity of the subsequent alkali-activated reaction.
[0040] Furthermore, the kaolin, slag powder, and silica fume used in the dry mixing process are all fine powders. Dust masks and goggles must be worn during operation, and the feed port of the mixer must be equipped with a local dust removal device to prevent dust from flying and causing harm to the respiratory system of the operators.
[0041] Step 4: Prepare a potassium-based base activator solution.
[0042] Dissolve 4 to 8 parts by weight of potassium hydroxide in 18 to 28 parts by weight of deionized water, stir until completely dissolved and cool to room temperature, then add 15 to 25 parts by weight of potassium silicate with a modulus of 1.4 to 2.0 and stir until homogeneous to obtain a potassium-based base activator solution.
[0043] The potassium hydroxide mentioned above is industrial grade, with a purity of not less than 90% (mass fraction). The modulus of potassium silicate is defined as... The molar ratio, of which The modulus of potassium silicate. and These represent the molar amounts of silica and potassium oxide in the potassium silicate, respectively; the solid content of the potassium silicate is 30% to 45% (mass fraction), and the viscosity is 50 to 200 mPa·s (25°C). The final modulus of the potassium-based activator solution is preferably 1.5 to 1.8, within which the polymerization reactivity is moderate and the setting time is controllable.
[0044] It should be noted that this invention uses a potassium-based activator instead of a traditional sodium-based activator. The ionic radius of potassium ions (0.138 nm) is larger than that of sodium ions (0.102 nm). During the polymerization reaction, the larger potassium ions bind more tightly to the negatively charged sites in the aluminosilicate tetrahedral network framework, and are efficiently captured and fixed within the structural cavities by the network framework, significantly reducing the content of free alkali metal ions. This eliminates the problem of migration and precipitation of free alkali metal ions under humid and hot environments at the source, avoiding the damage to the matrix pore structure caused by carbonate crystallization pressure and the continuous erosion of the hydrophobic layer of the hydrophobic modified silica aerogel microspheres by alkali precipitates.
[0045] Furthermore, in the above potassium hydroxide dissolution step, the stirring rate is 200 to 400 rpm and the stirring time is 5 to 10 min. The potassium hydroxide dissolution process is exothermic, and the solution must be cooled to below 25°C before adding potassium silicate to prevent high temperature from accelerating the local condensation of silicates in the potassium silicate and affecting the uniformity of the potassium-based activator solution. After adding potassium silicate, continue stirring at 200 to 400 rpm for 5 to 10 min until the solution is uniform and transparent.
[0046] Furthermore, potassium hydroxide is a strong alkali and highly corrosive. When dissolving it, alkali-resistant protective gloves, goggles, and face shields must be worn, and the work surface must be covered with an alkali-resistant mat. The dissolution of potassium hydroxide is highly exothermic, so it must be added slowly in batches to deionized water while continuously stirring. It is forbidden to pour water into solid potassium hydroxide to prevent local boiling and splashing that could cause burns. Potassium silicate is a highly alkaline solution, and if it comes into contact with skin, it must be rinsed immediately with plenty of water.
[0047] Step 5: Prepare potassium-based polymer slurry.
[0048] Add the geopolymer precursor powder obtained in step 3 to the potassium-based activator solution obtained in step 4, and stir at 300 to 600 rpm for 3 to 5 minutes to obtain potassium-based geopolymer slurry.
[0049] The mass ratio of the aforementioned geopolymer precursor powder to the potassium-based activator solution is 1.5:1 to 2.5:1, preferably 1.8:1 to 2.2:1. The stirring time is preferably 4 minutes. Stirring is sufficient until the potassium-based polymer slurry is uniform and free of dry powder agglomerates; excessive stirring will introduce too many air bubbles, affecting the uniformity of subsequent foaming.
[0050] Furthermore, in the above feeding step, the geopolymer precursor powder is slowly added to the potassium-based alkali activator solution in batches, with an interval of 30 to 60 seconds between each batch, to prevent the concentrated addition of powder from causing excessive local alkali activation reaction and clumping; during the feeding process, the stirring speed is maintained at 300 to 400 rpm, and after the feeding is completed, the speed is increased to 500 to 600 rpm and stirring is continued until the potassium-based polymer slurry is uniform.
[0051] Step 6: Prepare foamed composite slurry.
[0052] Disperse 1 to 3 parts by weight of nano-zinc oxide in 4 to 12 parts by weight of deionized water and ultrasonically disperse for 10 to 20 minutes to obtain a nano-zinc oxide suspension. Add the nano-zinc oxide suspension to the potassium-based polymer slurry obtained in step 5 and stir at 300 to 600 rpm for 2 to 3 minutes to ensure uniform mixing. Then, add 15 to 25 parts by weight of hydrophobic modified silica aerogel microspheres obtained in step 2, 3 to 6 parts by weight of aluminum silicate short fibers, 0.3 to 1.0 parts by weight of 30% hydrogen peroxide aqueous solution, and 0.2 to 0.6 parts by weight of sodium dodecyl sulfate in sequence, and reduce the stirring speed to 100 to 200 rpm for 1 to 2 minutes to obtain a foamed composite slurry.
[0053] The primary particle size of the aforementioned nano-zinc oxide is 20 to 50 nm, and the specific surface area is 30 to 60 m². 2 / g, purity not less than 99.5% (mass fraction). Nano zinc oxide reacts with hydroxide ions in situ in an alkaline geopolymer slurry environment (pH 12 to 14) to form layered zincates. The zinc oxide and its condensation products are deposited in layered zincate deposits at micro-defects in the matrix pore walls, filling cracks and micropores, while blocking ion migration channels and further inhibiting the diffusion and migration of residual free ions. The preferred amount of nano zinc oxide is 1.5 to 2.5 parts by weight.
[0054] The aforementioned aluminosilicate short fibers have a diameter of 2 to 5 μm and a length of 3 to 10 mm. The content is 45% to 55% (mass fraction), and the temperature resistance is not lower than 1000℃. The short aluminum silicate fibers play a toughening and crack bridging role in the matrix, inhibiting the propagation of internal cracks in the board during the foaming process.
[0055] It should be noted that low-speed stirring avoids shear force damaging the nanoporous structure of the hydrophobically modified silica aerogel microspheres and the initial bubbles already formed. The stirring speed should not exceed 200 rpm, and the stirring time should not exceed 2 minutes. Sodium dodecyl sulfate is used as a foaming stabilizer to reduce the surface tension of the foamed composite slurry, ensuring a stable and uniform distribution of bubbles generated by the decomposition of hydrogen peroxide.
[0056] Furthermore, to improve the dispersion uniformity of nano-zinc oxide in alkaline slurry, 0.1 to 0.3 parts by weight of polycarboxylate superplasticizer can be added as a dispersing aid during the ultrasonic dispersion preparation of nano-zinc oxide suspension. The solid content of the polycarboxylate superplasticizer is 40% to 50% (mass fraction), and the water reduction rate is not less than 25%. The mass ratio of polycarboxylate superplasticizer to nano-zinc oxide is 0.1:1 to 0.3:3, preferably 0.1:1.5 to 0.2:2. The polycarboxylate superplasticizer molecules adsorb onto the surface of nano-zinc oxide particles, providing a steric hindrance effect, preventing nanoparticle aggregation, and making the distribution of layered zincates at micro-defects in the pore walls more uniform.
[0057] Furthermore, in the above-mentioned ultrasonic dispersion step, the ultrasonic frequency is 20 to 40 kHz, the ultrasonic power is 200 to 400 W, and the dispersion temperature is controlled at 15 to 25 °C to prevent the ultrasonic heat generation from causing the temperature of the nano zinc oxide suspension to rise prematurely and resulting in localized reactions on the surface of the nano zinc oxide particles.
[0058] Furthermore, the order of adding the above components must be strictly followed: the hydrophobic modified silica aerogel microspheres must be added before the hydrogen peroxide aqueous solution and sodium dodecyl sulfate to ensure that the hydrophobic modified silica aerogel microspheres are uniformly dispersed in the foamed composite slurry under low shear conditions; the hydrogen peroxide aqueous solution must be added last after the sodium dodecyl sulfate to prevent premature foaming from causing a large amount of gas to be generated in the foamed composite slurry before casting.
[0059] Furthermore, the decomposition rate of hydrogen peroxide in alkaline geopolymer slurries (pH 12 to 14) is significantly accelerated, posing a risk of rapid localized gas generation. After adding the hydrogen peroxide aqueous solution, it must be immediately stirred at a low speed of 100 to 200 rpm until homogeneous, and the pouring must be completed within 5 minutes to prevent premature large-scale foaming of the foamed composite slurry outside the mold. Direct contact between hydrogen peroxide and metallic ironware must be avoided during operation to prevent iron ions from catalyzing the violent decomposition of hydrogen peroxide. Stirring containers and tools must be made of stainless steel or polypropylene.
[0060] Furthermore, the aforementioned 30% hydrogen peroxide aqueous solution is a strong oxidizing agent, and is corrosive and flammable. When storing and using it, it must be kept away from reducing substances, organic matter and flammable materials. Operators must wear chemical-resistant protective gloves and splash-proof goggles. If hydrogen peroxide aqueous solution splashes onto the skin, it must be rinsed immediately with plenty of water. When handling nano zinc oxide powder, a dust mask must be worn to avoid inhaling nanoparticles.
[0061] Step 7: Pour and foam the product into shape.
[0062] Pre-lay alkali-resistant glass fiber mesh at the bottom of the mold, pour the foamed composite slurry obtained in step 6 into the mold, vibrate to vent for 2 to 4 minutes, let it stand at 45 to 60°C to foam and initially set for 3 to 5 hours to obtain a foamed board blank.
[0063] The mesh size of the aforementioned alkali-resistant glass fiber mesh is 4mm×4mm to 6mm×6mm, and the unit area mass is 120 to 180g / m². 2 , The content is not less than 14% (mass fraction). Alkali-resistant glass fiber mesh is laid at the bottom of the mold, serving as a reinforcing layer and crack-resistant layer after the sheet is formed. Vibration venting is performed using a vibration table with a frequency of 30 to 50 Hz and an amplitude of 0.3 to 0.5 mm. The preferred foaming temperature is 50 to 55℃, within which the hydrogen peroxide decomposition rate is moderate, resulting in uniform bubble size with a pore diameter of 0.5 to 2.0 mm. The pore diameter is determined by cross-sectional optical microscopy image analysis, using the average equivalent circle diameter of at least 50 pores.
[0064] Furthermore, in the above casting steps, the inner wall of the mold must be coated with a release agent in advance, and the top of the mold should be sealed with plastic wrap after casting to prevent moisture evaporation during the initial setting stage of foaming from forming a hard shell on the surface of the foamed board and affecting the uniformity of the cells; the temperature of the foaming molding environment should be controlled at 20 to 30°C and the relative humidity should not be lower than 60%.
[0065] Step 8, dry the area.
[0066] The foamed board obtained in step 7 is cured at 70-85℃ and 70-90% relative humidity for 48-96 hours. After demolding, it is dried in an oven at 105-120℃ for 6-10 hours to obtain the geopolymer aerogel microsphere composite board. Drying continues until the moisture content of the geopolymer aerogel microsphere composite board is below 3% (mass fraction). The moisture content is determined by the drying and weighing method, and calculated as the ratio of the mass difference before and after drying to the mass before drying.
[0067] Moist heat curing promotes the continuous polymerization reaction, allowing the aluminosilicate precursor to fully dissolve and react with the potassium-based activator solution to form a complete three-dimensional network structure. The preferred curing temperature is 75 to 80°C, and the preferred curing time is 72 hours. Curing temperatures above 85°C will accelerate moisture evaporation, leading to shrinkage cracks on the substrate surface. The preferred drying temperature is 110°C.
[0068] Furthermore, in the above-mentioned damp heat curing steps, the heating rate is controlled at 1 to 3℃ / min, from room temperature to the target curing temperature, so as to avoid the rapid heating causing a temperature gradient inside the foamed board and resulting in thermal stress cracking; the relative humidity of the curing environment is maintained by a humidification device, and the surface moisture content of the foamed board is checked every 12 hours to ensure that the surface of the foamed board does not experience water loss and shrinkage.
[0069] Step 9, surface sealing coating.
[0070] The surface of the geopolymer aerogel microsphere composite plate obtained in step 8 is lightly polished to reduce the surface roughness. The range is 5 to 15 μm, of which The arithmetic mean roughness is given. An organosilicon-acrylic acid copolymer emulsion is uniformly dipped into the surface of the geopolymer aerogel microsphere composite board at a coating amount of 8 to 15 parts by weight to form a hydrophobic sealing layer. The board is then dried in an oven at 60 to 80°C for 2 to 4 hours to obtain a fireproof, soundproof, and heat-insulating board.
[0071] The above-mentioned organosilicon-acrylic copolymer emulsion has a solid content of 40% to 55% (mass fraction), a viscosity of 50 to 200 mPa·s (25°C), and a glass transition temperature of... The temperature ranges from -5 to 15°C, among which The glass transition temperature of the silicone-acrylic copolymer emulsion after film formation is defined as 15% to 30% (by total copolymer mass). The silicone segments provide hydrophobicity and weather resistance, while the acrylic segments provide film formation and adhesion. The preferred coating amount is 10 to 12 parts by weight (based on the emulsion), and the dry film thickness is 80 to 150 μm. The dry film thickness is measured using a coating thickness gauge (magnetic induction method, GB / T 4956), taking the average of at least 5 measurement points. The hydrophobic sealing layer prevents external moisture from penetrating the interior of the geopolymer aerogel microsphere composite plate, reducing the driving force for the migration of residual ions carried by moisture under humid and hot conditions. Together with the internal potassium-based network for potassium fixation and nano-zinc oxide to block ion channels, it constitutes a multi-layered protective system.
[0072] Furthermore, in the above-mentioned sanding step, sandpaper with a grit of 120 to 180 is used, and compressed air is used to remove surface dust after sanding; in the dip coating step, the surface temperature of the geopolymer aerogel microsphere composite plate should be preheated to 30 to 40°C to improve the wetting and spreading properties of the organosilicon acrylic copolymer emulsion on the surface of the geopolymer aerogel microsphere composite plate, and ensure that the coating is uniform and without any missed areas; in the drying step, the heating rate is controlled at 2 to 5°C / min, the drying temperature is preferably 70°C, and the drying time is preferably 3 hours.
[0073] Furthermore, the final product of the above-mentioned fireproof, soundproof, and heat-insulating board is characterized by the following methods: thermal conductivity is determined by the heat flow meter method (GB / T 10294); sound insulation is determined by the standing wave tube method (GB / T 18696.1); combustion performance rating is determined by the non-combustibility test of building materials (GB / T 5464); compressive strength is determined by the uniaxial compression test (GB / T 50081); and the microstructure of the board is observed by scanning electron microscopy to examine the cross-sectional morphology.
[0074] Furthermore, the dust generated during the above-mentioned grinding steps must be collected using a local dust extraction device, and operators must wear dust masks; the dust collected during grinding is inorganic solid waste and must be collected centrally and disposed of as general industrial solid waste.
[0075] Furthermore, the main waste generated during the preparation process of this invention is handled as follows: the organic waste liquid containing hexane, ethanol, and methanol generated in steps 1 and 2 must be collected separately and handed over to a qualified hazardous waste treatment institution for treatment; the distillation recovery of hexane and the recycling of mineral oil in step 2 reduces the consumption of organic solvents and reflects the principle of raw material recycling; the small amount of alkaline waste liquid generated in step 4 during the dissolution of potassium hydroxide and the preparation of potassium-based activator solution must be neutralized to a pH value of 6 to 9 before it can be discharged; the decomposition products of hydrogen peroxide in step 6 are water and oxygen, and no toxic waste gas is generated; no toxic catalysts containing heavy metals are used in the entire process, and the solid waste is mainly a small amount of waste alkali-resistant glass fiber mesh scraps and waste sandpaper, which are disposed of as general industrial solid waste.
[0076] This invention addresses the technical problems of alkaline erosion and alkaline coupling degradation of silica aerogel microspheres through the synergistic combination of hydrophobically modified silica aerogel microspheres, potassium-based base activator system, and nano zinc oxide.
[0077] In terms of aerogel protection: Methyltrimethoxysilane forms a covalently bonded hydrophobic monolayer on the inner wall and outer surface of the nanopores of silica aerogel microspheres, enabling the surface contact angle of the hydrophobically modified silica aerogel microspheres to reach 140° to 155°. When the hydrophobically modified silica aerogel microspheres are dispersed in an alkaline slurry, the droplet repulsion effect generated by the high contact angle prevents the alkaline solution from penetrating into the nanopores through capillary action, thereby avoiding the dissolution of the framework and collapse of the pore structure caused by alkaline erosion. This allows the hydrophobically modified silica aerogel microspheres to maintain ultra-low thermal conductivity during the service life of the substrate.
[0078] In eliminating alkali bloom: Potassium ions, due to their large ionic radius, are captured and fixed by the structural cavities of the aluminosilicate tetrahedral network framework during the polymerization reaction, reducing the content of free alkali metal ions. Activated alumina micropowder provides an additional aluminum source, promoting an increase in the proportion of aluminum-oxygen tetrahedra in the network, forming a highly cross-linked framework, enhancing the binding ability of alkali metal ions and improving the water resistance of the matrix. Nano-zinc oxide generates layered zincates in situ in an alkaline environment, filling micro-defects in the pore walls and blocking ion migration channels. These three methods reduce the driving force of alkali bloom from three levels: ion fixation, channel blocking, and structural densification, avoiding the damage to the matrix and the hydrophobic layer of the hydrophobic modified silica aerogel microspheres caused by carbonate crystallization pressure.
[0079] In terms of functional synergy: the foamed pore structure and hydrophobically modified silica aerogel microspheres form multiple acoustic impedance abrupt change interfaces, enhancing the reflection and dissipation of sound waves at different media interfaces, thus achieving sound insulation. The geopolymer matrix itself is an inorganic non-combustible material, which, combined with the toughening of aluminum silicate short fibers and the reinforcement of alkali-resistant glass fiber mesh, ensures the fire resistance and structural integrity of the board. The above multi-layered protection system enables the fireproof, soundproof, and heat-insulating board to maintain the stability of its fireproof, soundproof, and heat-insulating functions in humid and hot service environments, overcoming the problem of continuous deterioration of heat insulation and sound insulation performance in existing technologies.
[0080] Example 1 Step 1: Dissolve 15 parts of tetraethyl orthosilicate in 40 parts of anhydrous ethanol, add 0.1 parts of oxalic acid and 8 parts of deionized water (tetraethyl orthosilicate to deionized water molar ratio 1:3), and stir at 40℃ for 4 hours, controlling the pH of the silica sol to 2.0 to form a silica sol. The viscosity of the continuous phase of mineral oil is 5 mPa·s (25℃). Emulsification is carried out under a nitrogen atmosphere (nitrogen flow rate 0.1 L / min) with stirring at 800 rpm, aiming for a gel droplet size of 100 μm. After emulsification, allow to stand at 25℃ for 12 hours to complete gelation. Replace with ethanol twice (4 hours each time) and then with n-hexane twice (4 hours each time), both at 25℃. Dry under supercritical carbon dioxide conditions: temperature 40℃, pressure 10 MPa. Silica aerogel microspheres were obtained by applying pressure at a flow rate of 50 L / h, a pressurization rate of 0.2 MPa / min, a depressurization rate of 0.1 MPa / min, and a drying time of 4 h. The hexane-substituted solution was recovered by vacuum distillation at 60 °C and 0.03 MPa.
[0081] Step 2: Incubate silica aerogel microspheres at 60°C and a vacuum degree of not less than [missing information]. Vacuum drying at MPa for 2 h. Under a nitrogen atmosphere (nitrogen flow rate 0.05 L / min), a modification solution (3% by mass) was prepared by dissolving 3 parts of methyltrimethoxysilane in 97 parts of n-hexane. The silica aerogel microspheres were then immersed in the modification solution and reacted at 25 °C for 2 h. After filtration, the microspheres were washed three times with n-hexane (each time using 3 times the mass of the aerogel microspheres) and dried in an oven at 60 °C for 1 h to obtain hydrophobically modified silica aerogel microspheres. The filtrate was separated by distillation: methanol was distilled off at atmospheric pressure and 64 °C, and n-hexane was recovered at atmospheric pressure and 68 °C.
[0082] Step 3: Take 50 parts of metakaolin (calcined at 700℃), Content 40%, Content 50%, specific surface area 12m² 2 / g, =3μm), 15 parts of slag powder, and 5 parts of activated alumina powder (specific surface area 150m²). 2 / g, =1μm), 8 parts of silica fume (specific surface area 18m²) 2 / g, =0.1μm) was dry-mixed in a mixer at 100rpm for 10min to obtain geopolymer precursor powder.
[0083] Step 4: Dissolve 4 parts of potassium hydroxide in 18 parts of deionized water, stir at 200 rpm for 5 min, cool to below 25℃, then add 15 parts of potassium silicate with a modulus of 1.4, a solid content of 30%, and a viscosity of 50 mPa·s, and continue stirring at 200 rpm for 5 min until uniform and transparent, to obtain a potassium-based base activator solution with a final modulus of 1.5.
[0084] Step 5: Add the geopolymer precursor powder obtained in Step 3 to the potassium-based alkali activator solution obtained in Step 4 in batches (the mass ratio of powder to alkali activator is 1.5:1, and the addition interval is 30s). The stirring speed is 300rpm during addition, and after the addition is completed, the speed is increased to 500rpm and stirring is continued. The total stirring time is 3min to obtain potassium-based geopolymer slurry.
[0085] Step 6: Add 1 part of nano zinc oxide (primary particle size 20nm, specific surface area 30m²) 2 / g) and 0.1 parts of polycarboxylate superplasticizer (solid content 40%, mass ratio of nano zinc oxide 0.1:1) were dispersed in 4 parts of deionized water and ultrasonically dispersed at 20kHz, 200W for 10min at a dispersion temperature of 15℃ to obtain a nano zinc oxide suspension. The suspension was added to the potassium-based polymer slurry obtained in step 5 and stirred at 300rpm for 2min to mix evenly. Then, 15 parts of hydrophobic modified silica aerogel microspheres and 3 parts of aluminum silicate short fibers (diameter 2μm, length 3mm) obtained in step 2 were added sequentially. 0.3 parts of a hydrogen peroxide aqueous solution with a content of 45% and a mass fraction of 30% and 0.2 parts of sodium dodecyl sulfate were mixed at a low speed of 100 rpm for 1 min to obtain a foamed composite slurry.
[0086] Step 7: Pre-lay a mesh with a size of 4mm×4mm and a unit area mass of 120g / m² at the bottom of the mold. 2 The alkali-resistant glass fiber mesh was used to pour the foamed composite slurry into the mold, vibrate and degas for 2 minutes at a frequency of 30Hz and an amplitude of 0.3mm, and then let it stand at 45℃ and an ambient temperature of 20℃ for 3 hours to foam and initially set, thus obtaining the foamed board blank.
[0087] Step 8: The foamed board blank is heated to the target temperature at a rate of 1℃ / min under the conditions of 70℃ and 70% relative humidity and cured for 48h. After demolding, it is dried in an oven at 105℃ for 6h to obtain the geopolymer aerogel microsphere composite board.
[0088] Step 9: Use 120-grit sandpaper to sand the surface of the board to the desired roughness. =5μm, preheated to 30℃, with a solid content of 40% and a viscosity of 50mPa·s, A silicone-acrylic copolymer emulsion with a content of 15% silicone monomer and a temperature of -5℃ was uniformly dipped into the surface of the board at a coating amount of 8 parts. The temperature was raised to 60℃ at a heating rate of 2℃ / min and then dried for 2 hours. The dry film thickness was 80μm, and the fireproof, soundproof and heat-insulating board was obtained, which was marked as sample 1.
[0089] Example 2 Step 1: Dissolve 20 parts of tetraethyl orthosilicate in 50 parts of anhydrous ethanol, add 0.2 parts of oxalic acid and 10 parts of deionized water (tetraethyl orthosilicate to deionized water molar ratio 1:4), and stir at 45℃ for 6 hours, controlling the pH of the silica sol to 2.5 to form a silica sol. The viscosity of the mineral oil continuous phase is 10 mPa·s (25℃). Emulsify under a nitrogen atmosphere (nitrogen introduction rate 0.2 L / min) by stirring at 1100 rpm, aiming for a gel droplet size of 200 μm. After emulsification, allow to stand at 30℃ for 18 hours to complete gelation. Replace with ethanol twice (6 hours each time) and n-hexane twice (6 hours each time), with the replacement temperature at 30℃. Dry under supercritical carbon dioxide conditions: temperature 45℃, pressure 12 MPa. Silica aerogel microspheres were obtained by applying pressure at a flow rate of 85 L / h, a pressurization rate of 0.35 MPa / min, a depressurization rate of 0.2 MPa / min, and a drying time of 5.5 h. The hexane-substituted solution was recovered by vacuum distillation at 65 °C and 0.04 MPa.
[0090] Step 2: Incubate silica aerogel microspheres at 65°C and a vacuum degree of not less than [missing information]. Vacuum drying at MPa for 3 h. Under a nitrogen atmosphere (nitrogen flow rate 0.1 L / min), a modification solution (5% by mass) was prepared by dissolving 5 parts of methyltrimethoxysilane in 95 parts of n-hexane. The silica aerogel microspheres were then immersed in the modification solution and reacted at 30 °C for 3 h. After filtration, the microspheres were washed three times with n-hexane (each time using 4 times the mass of the aerogel microspheres) and dried in an oven at 70 °C for 1.5 h to obtain hydrophobically modified silica aerogel microspheres. The filtrate was separated by distillation: methanol was distilled off at atmospheric pressure and 65 °C, and n-hexane was recovered at atmospheric pressure and 69 °C.
[0091] Step 3: Take 60 parts of metakaolin (calcined at 775℃), Content 42.5%, Content 52.5%, specific surface area 16m² 2 / g, =5μm), 20 parts of slag powder, and 8 parts of activated alumina powder (specific surface area 215m²). 2 / g, =3μm), 11 parts of silica fume (specific surface area 21m²) 2 / g, =0.2μm) was dry-mixed in a mixer at 150rpm for 15min to obtain geopolymer precursor powder.
[0092] Step 4: Dissolve 6 parts of potassium hydroxide in 23 parts of deionized water, stir at 300 rpm for 7.5 min, cool to below 25°C, then add 20 parts of potassium silicate with a modulus of 1.6, a solid content of 37.5%, and a viscosity of 125 mPa·s. Continue stirring at 300 rpm for 7.5 min until uniform and transparent to obtain a potassium-based base activator solution with a final modulus of 1.65.
[0093] Step 5: Add the geopolymer precursor powder obtained in Step 3 to the potassium-based alkali activator solution obtained in Step 4 in batches (the mass ratio of powder to alkali activator is 2.0:1, and the addition interval is 45s). The stirring speed is 350rpm during addition, and after the addition is completed, the speed is increased to 550rpm and stirring is continued. The total stirring time is 4min to obtain potassium-based geopolymer slurry.
[0094] Step 6: Add 2 portions of nano zinc oxide (primary particle size 35nm, specific surface area 45m²) 2 A nano zinc oxide suspension was prepared by dispersing 0.2 parts of polycarboxylate superplasticizer (solid content 45%, mass ratio of nano zinc oxide to zinc oxide 0.1:1) in 8 parts of deionized water and ultrasonically dispersing at 30 kHz, 300 W for 15 min at a dispersion temperature of 20 °C. The suspension was added to the potassium-based polymer slurry obtained in step 5 and stirred at 450 rpm for 2.5 min until homogeneous. Then, 20 parts of hydrophobic modified silica aerogel microspheres, 4.5 parts of aluminum silicate short fibers (diameter 3.5 μm, length 6.5 mm, content 50%), 0.65 parts of 30% hydrogen peroxide aqueous solution and 0.4 parts of sodium dodecyl sulfate were added sequentially, and the mixture was stirred at a low speed of 150 rpm for 1.5 min to obtain a foamed composite slurry.
[0095] Step 7: Pre-lay a mesh with a size of 5mm × 5mm and a unit area mass of 150g / m² at the bottom of the mold. 2 The alkali-resistant glass fiber mesh was used to pour the foamed composite slurry into the mold, vibrate and degas for 3 minutes at a frequency of 40Hz and an amplitude of 0.4mm, and then let it stand at 52℃ and an ambient temperature of 25℃ for 4 hours to foam and initially set, thus obtaining the foamed board blank.
[0096] Step 8: The foamed board blank is heated to the target temperature at a rate of 2℃ / min under the conditions of 77℃ and 80% relative humidity and cured for 72h. After demolding, it is dried in an oven at 110℃ for 8h to obtain the geopolymer aerogel microsphere composite board.
[0097] Step 9: Use 150-grit sandpaper to sand the surface of the board to the desired roughness. =10μm, preheated to 35℃, with a solid content of 47.5% and a viscosity of 125mPa·s, An organosilicon acrylic copolymer emulsion with a content of 22.5% organosilicon monomer and a temperature of 5℃ was uniformly dipped into the surface of the board at a coating amount of 11 parts. The temperature was raised to 70℃ at a heating rate of 3℃ / min and then dried for 3 hours. The dry film thickness was 115μm, and the fireproof, soundproof and heat-insulating board was obtained, which was marked as sample 2.
[0098] Example 3 Step 1: Dissolve 25 parts of tetraethyl orthosilicate in 60 parts of anhydrous ethanol, add 0.3 parts of oxalic acid and 12 parts of deionized water (tetraethyl orthosilicate to deionized water molar ratio 1:5), and stir at 50℃ for 8 hours, controlling the pH of the silica sol to 3.5 to form a silica sol. The viscosity of the mineral oil continuous phase is 15 mPa·s (25℃). Emulsify under a nitrogen atmosphere (nitrogen introduction rate 0.3 L / min) at 1500 rpm, aiming for a gel droplet size of 300 μm. After emulsification, allow to stand at 35℃ for 24 hours to complete gelation. Replace with ethanol three times (8 hours each time) and n-hexane three times (8 hours each time), with each replacement temperature at 35℃. Dry under supercritical carbon dioxide conditions: temperature 50℃, pressure 14 MPa. Silica aerogel microspheres were obtained by applying pressure at a flow rate of 120 L / h, a pressurization rate of 0.5 MPa / min, a depressurization rate of 0.3 MPa / min, and a drying time of 8 h. The hexane-substituted solution was recovered by vacuum distillation at 70 °C and 0.05 MPa.
[0099] Step 2: Incubate silica aerogel microspheres at 70°C and a vacuum degree of not less than [missing information]. Vacuum drying at MPa for 4 h. Under a nitrogen atmosphere (nitrogen flow rate 0.15 L / min), a modification solution (8% by mass) was prepared by dissolving 8 parts of methyltrimethoxysilane in 92 parts of n-hexane. The silica aerogel microspheres were then immersed in the modification solution and reacted at 35 °C for 4 h. After filtration, the microspheres were washed three times with n-hexane (each time using 5 times the mass of the aerogel microspheres) and dried in an oven at 80 °C for 2 h to obtain hydrophobically modified silica aerogel microspheres. The filtrate was separated by distillation: methanol was distilled off at atmospheric pressure and 66 °C, and n-hexane was recovered at atmospheric pressure and 70 °C.
[0100] Step 3: Take 70 parts of metakaolin (calcined at 850℃), Content 45%, Content 55%, specific surface area 20m² 2 / g, =8μm), 25 parts of slag powder, and 12 parts of activated alumina powder (specific surface area 280m²). 2 / g, =5μm), 15 parts of silica fume (specific surface area 25m²) 2 / g, =0.3μm) was dry-mixed in a mixer at 200rpm for 20min to obtain geopolymer precursor powder.
[0101] Step 4: Dissolve 8 parts of potassium hydroxide in 28 parts of deionized water, stir at 400 rpm for 10 min, cool to below 25°C, then add 25 parts of potassium silicate with a modulus of 2.0, a solid content of 45%, and a viscosity of 200 mPa·s, and continue stirring at 400 rpm for 10 min until uniform and transparent, to obtain a potassium-based base activator solution with a final modulus of 1.8.
[0102] Step 5: Add the geopolymer precursor powder obtained in Step 3 to the potassium-based alkali activator solution obtained in Step 4 in batches (the mass ratio of powder to alkali activator is 2.5:1, and the addition interval is 60s). The stirring speed is 400rpm during addition, and after the addition is completed, the speed is increased to 600rpm and stirring is continued. The total stirring time is 5min to obtain potassium-based geopolymer slurry.
[0103] Step 6: Add 3 portions of nano zinc oxide (primary particle size 50nm, specific surface area 60m²) 2 / g) and 0.3 parts of polycarboxylate superplasticizer (solid content 50%, mass ratio of nano zinc oxide 0.1:1) were dispersed in 12 parts of deionized water and ultrasonically dispersed at 40kHz, 400W for 20min at a dispersion temperature of 25℃ to obtain a nano zinc oxide suspension. The suspension was added to the potassium-based polymer slurry obtained in step 5 and stirred at 600rpm for 3min to mix evenly. Then, 25 parts of hydrophobic modified silica aerogel microspheres and 6 parts of aluminum silicate short fibers (diameter 5μm, length 10mm) obtained in step 2 were added sequentially. 1.0 part of a hydrogen peroxide aqueous solution with a content of 55% and a mass fraction of 30% and 0.6 parts of sodium dodecyl sulfate were mixed at a low speed of 200 rpm for 2 min to obtain a foamed composite slurry.
[0104] Step 7: Pre-lay a mesh with a size of 6mm×6mm and a unit area mass of 180g / m² at the bottom of the mold. 2 The alkali-resistant glass fiber mesh was used to pour the foamed composite slurry into the mold, vibrate and degas for 4 minutes at a frequency of 50Hz and an amplitude of 0.5mm, and then let it stand at 60℃ and an ambient temperature of 30℃ for 5 hours to foam and initially set, thus obtaining the foamed board blank.
[0105] Step 8: The foamed board blank is heated to the target temperature at a rate of 3℃ / min under conditions of 85℃ and 90% relative humidity and then cured for 96h. After demolding, it is dried in an oven at 120℃ for 10h to obtain the geopolymer aerogel microsphere composite board.
[0106] Step 9: Use 180-grit sandpaper to sand the surface of the board to the desired roughness. =15μm, preheated to 40℃, with a solid content of 55% and a viscosity of 200mPa·s, A silicone acrylic copolymer emulsion with a content of 30% silicone monomer and a temperature of 15℃ was uniformly dipped into the surface of the board at a coating amount of 15 parts. The temperature was raised to 80℃ at a heating rate of 5℃ / min and then dried for 4 hours. The dry film thickness was 150μm, and the fireproof, soundproof and heat-insulating board was obtained, which was marked as sample 3.
[0107] Example 4 Steps 1 to 9 are basically the same as in Example 2. The following parameters are taken from the minimum end of each preferred range: emulsification speed 1000 rpm, supercritical drying time 5 h, 4 parts methyltrimethoxysilane (96 parts n-hexane, 4% by mass), modification temperature 28℃, modification time 2.5 h, 7 parts activated alumina micro powder, final modulus of potassium-based alkali activator solution 1.5, powder to alkali activator mass ratio 1.8:1, 1.5 parts nano zinc oxide (0.15 parts polycarboxylate superplasticizer, mass ratio to nano zinc oxide 0.1:1), foaming temperature 50℃, curing temperature 75℃, and coating amount of organosilicon acrylic copolymer emulsion 10 parts. The remaining parameters are the same as in Example 2. A fireproof, soundproof, and heat-insulating board was obtained and marked as Sample 4.
[0108] Example 5 Steps 1 to 9 are basically the same as in Example 2. The following parameters are taken as the maximum endpoints of each preferred range: emulsification speed 1200 rpm, supercritical drying time 6 h, 6 parts methyltrimethoxysilane (94 parts n-hexane, 6% by mass), modification temperature 32℃, modification time 3.5 h, 10 parts activated alumina micro powder, final modulus of potassium-based alkali activator solution 1.8, powder to alkali activator mass ratio 2.2:1, 2.5 parts nano zinc oxide (0.25 parts polycarboxylate superplasticizer, mass ratio to nano zinc oxide 0.1:1), foaming temperature 55℃, curing temperature 80℃, and coating amount of organosilicon acrylic copolymer emulsion 12 parts. The remaining parameters are the same as in Example 2. A fireproof, soundproof, and heat-insulating board was obtained and marked as sample 5.
[0109] Comparative Example 1 The hydrophobic modification step in step 2 is omitted. The silica aerogel microspheres obtained in step 1 are used directly in step 6 to replace the hydrophobically modified silica aerogel microspheres without modification by methyltrimethoxysilane. The parameters of the remaining steps 1 and steps 3 to 9 are exactly the same as in Example 2. A fireproof, soundproof, and heat-insulating board is obtained and marked as control sample C1.
[0110] Comparative Example 2 In step 4, potassium hydroxide was replaced with an equimolar amount of sodium hydroxide, and potassium silicate was replaced with an equimolar amount of sodium silicate (modulus 1.6, solid content 37.5%, viscosity 125 mPa·s) to prepare a sodium-based alkali activator solution. The modulus of the final alkali activator solution remained unchanged at 1.65. The parameters of the remaining steps 1 to 3 and steps 5 to 9 were exactly the same as in Example 2. A fireproof, soundproof, and heat-insulating board was obtained and marked as control sample C2.
[0111] Comparative Example 3 In step 6, the preparation steps of nano-zinc oxide and its suspension are omitted, and nano-zinc oxide and polycarboxylate superplasticizer are not added. The corresponding deionized water (8 parts) is directly added to the potassium-based polymer slurry. The parameters of the remaining steps 1 to 5 and steps 7 to 9 are exactly the same as in Example 2. A fireproof, soundproof, and heat-insulating board is obtained and marked as control sample C3.
[0112] Experimental test: This experiment characterizes the performance of samples 1 to 5 obtained in Examples 1 to 5 to verify that the fireproof, soundproof, and heat-insulating boards prepared by the present invention within the parameter range have excellent heat insulation, sound insulation, and fireproof performance. At the same time, through comparative experiments between Examples 1 to 3 and Example 2, the necessity of the three key technical means of hydrophobic modification, potassium-based alkali activator, and nano zinc oxide for the performance of the boards is verified. The focus is on examining the thermal conductivity stability of hydrophobic modified silica aerogel microspheres in an alkaline matrix, the inhibitory effect of the potassium-based system on efflorescence after humid heat aging, and the blocking effect of nano zinc oxide on ion migration channels.
[0113] Experimental sample preparation: Fireproof, soundproof, and heat-insulating boards were prepared according to the parameters of Examples 1 to 5 and Comparative Examples 1 to 3, with uniform dimensions of 300mm × 300mm × 50mm. After curing and drying, each sample was placed in a standard laboratory environment (temperature 23±2℃, relative humidity 50±5%) for 24 hours before performance testing. Before the damp heat aging test, the samples were placed in a damp heat chamber at 70℃ and 95% relative humidity for 28 days to simulate a damp heat service environment.
[0114] Experimental conditions: Initial performance tests were conducted under standard conditions (23±2℃, 50±5%RH); performance tests after damp heat aging were conducted after the samples were removed and cooled to 23℃. All performance tests were repeated three times and the average value was taken.
[0115] Experimental steps: Step 1, Thermal conductivity determination: The initial thermal conductivity of the sample and the thermal conductivity after 28 days of damp heat aging were determined using the heat flow meter method (GB / T 10294) at an average temperature of 25℃.
[0116] Step 2, sound insulation measurement: The standing wave tube method (GB / T 18696.1) is used, with a test frequency range of 500 to 2000 Hz. The sound insulation at the center frequency of 1000 Hz is taken as the representative value. The initial sound insulation and the sound insulation after 28 days of damp heat aging are measured respectively.
[0117] Step 3, Determination of flammability rating: The flammability rating of the sample is determined by using the non-combustible building materials test (GB / T 5464).
[0118] Step 4, compressive strength determination: Uniaxial compression test (GB / T 50081) was adopted, with a loading rate of 0.5 MPa / min, to determine the initial compressive strength and the compressive strength after 28 days of damp heat aging.
[0119] Step 5, Efflorescence Rating: After aging the sample at 70℃ and 95%RH for 28 days, visually inspect the carbonate precipitation on the board surface and rate it according to the proportion of the precipitation area to the total board area: Grade 0 is no precipitation (0%), Grade 1 is slight (area ratio less than 5%), Grade 2 is moderate (area ratio 5% to 20%), and Grade 3 is severe (area ratio greater than 20%).
[0120] Step Six: Characterization of Alkali Erosion of Aerogel Microspheres: Cross-sectional fragments of each sample after 28 days of wet heat aging were collected. The pore structure retention of the aerogel microspheres was observed using a scanning electron microscope (SEM). The specific surface area of the aerogel microspheres separated from the substrate was determined using the BET method. The degree of alkali erosion was characterized by the specific surface area retention rate (the ratio of the specific surface area after aging to the initial specific surface area). The calculation formula is as follows:
[0121] in, Specific surface area retention rate The specific surface area of the aerogel microspheres after aging ( ), The initial specific surface area of the aerogel microspheres ( ).
[0122] See experimental or test results Figures 2-8 And as shown in the table below: Table 1 Key parameters of raw material formulations for Examples 1 to 5 and Comparative Examples 1 to 3
[0123] As shown in Table 1, Examples 1 to 5 all possess the three technical features of hydrophobic modified aerogel microspheres, potassium-based base activator, and nano zinc oxide; Comparative Examples 1 to 3 lack one of these features respectively, forming a single-factor control experiment that can be used to independently evaluate the contribution of each technical means.
[0124] Table 2 Comparison of initial performance and performance after 28 days of damp heat aging
[0125] As shown in Table 2, Examples 1 to 5 (Samples 1 to 5) that meet all the technical features of this invention exhibited thermal conductivity changes of less than 10% after 28 days of damp heat aging, a sound insulation decrease of no more than 1.0 dB, a compressive strength retention rate of over 88%, and a combustion performance rating of A1. In comparison, Control Sample C1 (omitting hydrophobic modification) showed a thermal conductivity change rate of 57.8% after aging, approximately 7.5 times higher than Example 2 (Sample 2), with a sound insulation decrease of 5.4 dB; Control Sample C2 (sodium-based system) showed a thermal conductivity change rate of 24.4% after aging, approximately 2.6 times higher than Sample 2; and Control Sample C3 (without nano-zinc oxide) showed a thermal conductivity change rate of 40.9% after aging, approximately 5.0 times higher than Sample 2. These data demonstrate that the three technical methods play an irreplaceable role in maintaining performance stability after damp heat aging.
[0126] Table 3 Alkali bloom rating and specific surface area retention rate of aerogel microspheres after damp heat aging
[0127] As shown in Table 3, the alkali bloom level of samples 1 to 5 was 0 after 28 days of damp heat aging, and the specific surface area retention rate of aerogel microspheres was between 91% and 93%. This indicates that the hydrophobic modification layer effectively prevented the erosion of the aerogel nanoporous structure by alkaline solution, and the synergistic effect of the potassium-based system and nano-zinc oxide effectively inhibited the migration and precipitation of alkali metal ions. The specific surface area retention rate of control sample C1 (unmodified) was only 43.0%, which was about 53.5 percentage points lower than that of sample 2 in Example 2, proving that hydrophobic modification is the core means to protect the porous structure of aerogel. The alkali bloom level of control sample C2 (sodium-based system) reached 2, and the specific surface area retention rate was 75.1%, which was about 17.4 percentage points lower than that of sample 2, proving that potassium-based alkali activators are indispensable for reducing free alkali metal ions and inhibiting alkali blooming from the source. The control sample C3 (without nano zinc oxide) also had an alkali bloom level of 2, with a specific surface area retention rate of 65.7%, which was about 26.8 percentage points lower than that of sample 2. This proves that the in-situ formation of layered zincates by nano zinc oxide to block ion migration channels plays an important role in further inhibiting alkali bloom and protecting the hydrophobic modified layer.
[0128] Based on the above experimental results, this invention achieves the following technical effects through the synergistic combination of three technologies: hydrophobically modified silica aerogel microspheres, a potassium-based alkali activator system, and nano-zinc oxide. Firstly, hydrophobic modification forms a covalently bonded methylsilane monolayer on the inner wall of the aerogel nanopores, achieving a water contact angle of 140° to 155°. This effectively prevents alkaline solutions from penetrating the nanopores, maintaining the specific surface area retention rate of the aerogel microspheres above 91% after hygrothermal aging, and controlling the change rate of thermal conductivity to within 10%, thus solving the problem of aerogel pore structure collapse caused by alkali erosion. Secondly, the potassium-based alkali activator... Potassium ions in the efflorescence agent are effectively captured by the cavities of the aluminosilicate network framework due to their large ionic radius. Combined with activated alumina micropowder to enhance the network cross-linking degree, the content of free alkali metal ions is reduced from the source, so that the efflorescence level of the board is maintained at level 0 after humid heat aging. Thirdly, nano zinc oxide generates layered zincate in situ in an alkaline environment, filling micro-defects in the pore walls and blocking ion migration channels, further reducing the migration driving force of residual free ions. Together with the first two methods, it forms a multi-layered protection system, enabling the fireproof, soundproof and heat-insulating board to maintain the long-term stability of fireproof (A1 level), soundproof and heat-insulating functions in humid heat service environments.
[0129] The embodiments of the present invention have been described above. However, the embodiments are not limited to the specific implementation methods described above. The specific implementation methods described above are merely illustrative and not restrictive. Those skilled in the art can make more equivalent embodiments under the guidance of the present embodiments, and all of them are within the protection scope of the present embodiments.
Claims
1. A method for preparing a fireproof, soundproof, and heat-insulating board, characterized in that, Includes the following steps: Silica aerogel microspheres were prepared by sol-gel method and supercritical carbon dioxide drying, and then hydrophobically modified with methyltrimethoxysilane. Geopolymer precursor powder was obtained by dry mixing metakaolin, slag powder, activated alumina powder and silica fume; potassium hydroxide and potassium silicate were used to prepare a potassium-based activator solution. The geopolymer precursor powder is mixed with the potassium-based base activator solution to obtain potassium-based geopolymer slurry; After adding nano zinc oxide suspension to the potassium-based polymer slurry and mixing, hydrophobically modified silica aerogel microspheres, aluminum silicate short fibers, hydrogen peroxide aqueous solution and sodium dodecyl sulfate are added in sequence and stirred to obtain foamed composite slurry; The foamed composite slurry is poured and foamed into shape, and after curing and drying, the surface is coated with an organosilicon acrylic copolymer emulsion to form a hydrophobic sealing layer, thus obtaining a fireproof, soundproof and heat-insulating board.
2. The preparation method according to claim 1, characterized in that, The silica aerogel microspheres have a porosity of 90% to 95% and a specific surface area of 600 to 900 m². 2 / g, with an average pore size of 8 to 20 nm; the conditions for drying the supercritical carbon dioxide are a temperature of 40 to 50 °C, a pressure of 10 to 14 MPa, and a drying time of 4 to 8 h.
3. The preparation method according to claim 1, characterized in that, The hydrophobic modification uses a hexane solution of methyltrimethoxysilane as the modifying liquid, with a mass fraction of 3% to 8% for methyltrimethoxysilane. The modification reaction temperature is 25 to 35°C, and the reaction time is 2 to 4 hours. After modification, the water contact angle of the hydrophobic silica aerogel microspheres is 140° to 155°.
4. The preparation method according to claim 1, characterized in that, The geopolymer precursor powder comprises 50 to 70 parts by weight of metakaolin, 15 to 25 parts by weight of slag powder, 5 to 12 parts by weight of activated alumina powder, and 8 to 15 parts by weight of silica fume; the activated alumina powder is γ-phase alumina with a specific surface area of 150 to 280 m². 2 / g.
5. The preparation method according to claim 1, characterized in that, The potassium-based activator solution is prepared by dissolving 4 to 8 parts by weight of potassium hydroxide in 18 to 28 parts by weight of deionized water, cooling to room temperature, and then adding 15 to 25 parts by weight of potassium silicate with a modulus of 1.4 to 2.0; the solid content of the potassium silicate is 30% to 45%.
6. The preparation method according to claim 1, characterized in that, The primary particle size of the nano-zinc oxide is 20 to 50 nm, and the specific surface area is 30 to 60 m². 2 / g; The nano zinc oxide suspension is prepared by dispersing 1 to 3 parts by weight of nano zinc oxide in 4 to 12 parts by weight of deionized water and then ultrasonically dispersing for 10 to 20 minutes.
7. The preparation method according to claim 1, characterized in that, In the foamed composite slurry, the amount of hydrophobically modified silica aerogel microspheres is 15 to 25 parts by weight, the amount of aluminum silicate short fibers is 3 to 6 parts by weight, the amount of 30% hydrogen peroxide aqueous solution is 0.3 to 1.0 parts by weight, and the amount of sodium dodecyl sulfate is 0.2 to 0.6 parts by weight; the mass ratio of the geopolymer precursor powder to the potassium-based activator solution is 1.5:1 to 2.5:
1.
8. The preparation method according to claim 1, characterized in that, In the casting and foaming molding step, alkali-resistant glass fiber mesh cloth is pre-laid at the bottom of the mold, with a mesh size of 4mm×4mm to 6mm×6mm; the foaming temperature is 45 to 60℃, and the static foaming and initial setting time is 3 to 5 hours; the curing and drying includes curing at a temperature of 70 to 85℃ and a relative humidity of 70% to 90% for 48 to 96 hours, and after demolding, drying at 105 to 120℃ until the moisture content is less than 3%.
9. The preparation method according to claim 1, characterized in that, The solid content of the organosilicon acrylic copolymer emulsion is 40% to 55%, the coating amount is 8 to 15 parts by weight, and the dry film thickness is 80 to 150 μm; before coating, the surface of the plate is polished to an arithmetic mean roughness of 5 to 15 μm.
10. A fireproof, soundproof, and heat-insulating board prepared by the preparation method according to any one of claims 1 to 9.